AN ACCOUNT OF MACROBENTHIC INVERTEBRATE ASSEMBLAGES AND COMMUNITY STRUCTURE FROM THE RIVER GANGA, INDIA - THAKUR, VENKATESH RAMRAO; VERMA, HARIOM; JHA, DHARM NATH; ALAM, ABSAR; KUMAR, JEETENDRA; SHUKLA DAS, SHYAMAL CHANDRA; VERMA, SUSHIL KUMAR; MISHRA, SANDEEP KUMAR; SINGH, UPENDRA; DAS, BASANTA KUMAR (Journal of the Inland Fisheries Society of India, 2024)
The present study evaluated the habitat characteristics, including sediment and physicochemical properties with biological importance of the river Ganga, using macrobenthic invertebrate assemblages, laterally through an ecological variable. The studies were accompanied at the nine places (RG1 to RG9) in the upper and middle stretches of the Ganga River from March 2017 to January 2020. The present study recorded 35 taxa belonging to 4 classes (Insecta, Gastropoda, Bivalvia, and Annelida), 16 orders, and 29 families. It was observed that insects were dominated along the upper reaches (RG1 and RG3), whereas gastropods and bivalves were abundant at the middle reaches (RG4 to RG9). The mean value of total macrobenthic abundance, taxon richness, and Shannon and Simpson index was greater at RG5 to RG9 compared to sites RG1 to RG4. The findings from the present study revealed that the benthic macroinvertebrate’s assemblage pattern was designed by the habitat characteristics, including environmental variables, and through anthropogenic influences at various sampling sites.